Geodiversity and geological heritage characterisation in protected areas from NE Portugal: methodology and results - Dias, G. (2005)
We present the methodology and main results of a multidisciplinary research project carried out at two Natural Parks from NE Portugal: Montesinho and International Douro Natural Parks. This project aims to: (i) improve the geological knowledge in the MNP and IDNP; (ii) proceed with the inventory and characterisation of geosites; (iii) create scientific instruments to support a sustainable management of resources and territory; (iv) contribute to the increase of public awareness of Earth heritage.